The provision of pre-primary education in Mjini Magharibi Region-Zanzibar: Educational stakeholders’ perceptions - Ali, Ali Chai; Mligo, Ignasia Renatus; Nsolezi, Florentina Shaghembe (Eureka: Journal of Educational Research, 2023)
This paper explored educational stakeholder’s perceptions on the provision of Pre-Primary Education (PPE) in Zanzibar. The study employed qualitative methodology and a case study design where only PPE level among other levels of education was involved. A total number of 20 participants participated in the study where by 6 were pre-primary school teachers, 3 were pre-primary school head teachers, 5 were Quality Assurance Officer (QAO) from the Ministry of Education and 06 were parents. Data was generated by using focus group discussion and semi structured interviews. The results of the study revealed varied educational stakeholders’ perceptions on PPE which influenced by educational qualification of the participants, awareness, involvement, cost incurred, experience and expectations in PPE. The study concluded that the government, user institutions and people concerned in PPE should ensure that quality standards in terms of teachers, school environments, school administration, parent’s involvement, materials as well as the infrastructures and all the resources needed are improved and maintained for better teaching and learning in PPE. Also, the interactions between home (parents) and school (teachers) in PPE schools is unavoidable for better provision of PPE.